Evaluation of Flank Wear and Surface Roughness in Nanofluid-Assisted Machining of AISI 430 Ferritic Stainless Steel by FUCA MCDM Method - Yapan, Yusuf Furkan; Duman, Erkin; Dzhemilov, Eshreb; Uysal, Alper (SPRINGER INTERNATIONAL PUBLISHING AG, 2026)
This study investigates how different cutting conditions influence flank wear and surface roughness during the milling process of AISI 430 ferritic stainless steel. Experiments were performed using both uncoated and titanium nitride (TiN)coated tungsten carbide (WC) cutting tools under various conditions, including different flow rates (20 ml/h and 40 ml/h), and nano-MoS2 concentrations (0.5%, 1%, and 2% by weight). MQL significantly reduces wear of cutting tool and surface roughness in contrast to dry machining, with even greater improvements when nano-MoS2 is added. The TiN-coated WC tools demonstrated better performance, reducing flank wear by up to 22% and surface roughness by as much as 16% when contrasted with uncoated tools. The optimal performance was achieved with a 2% concentration of nano-MoS2 at a flow rate of 40 ml/h, resulting in a 43% decrease in tool wear and a 49% enhancement in surface quality. These findings underscore the effectiveness of TiN coatings and nano-MQL in enhancing tool life and surface finish, thus improving the machinability of AISI 430 ferritic stainless steel. Finally, optimum cutting parameters were selected and ranked using the FUCA multi-criteria decision-making method.
Keywords: Ferritic Stainless Steel; Vegetable Cutting Oil; MoS2 Based Nanofluid; FUCA; Engineering